2020
DOI: 10.1177/0300060520954763
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-29a/b expression in gestational diabetes mellitus and its influence on prognosis evaluation

Abstract: Objective To evaluate serum microRNA (miR)-29a/b expression in gestational diabetes mellitus (GDM) and its influence on neonatal prognosis. Methods This was a retrospective study including 68 pregnant women with GDM (GDM group) and 55 healthy pregnant women of similar age range and gestation period (healthy group). Results The area under the curve was 0.829 for the diagnosis of GDM using serum miR-29a expression, 0.857 for diagnosis using serum miR-29b expression, and 0.944 for combined diagnosis (using both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…This suggests that miR-29a is a negative regulator of serum glucose. A recent study supports the observation that GDM is characterized by lower circulating levels of miR-29a [71].…”
Section: Mirnassupporting
confidence: 76%
“…This suggests that miR-29a is a negative regulator of serum glucose. A recent study supports the observation that GDM is characterized by lower circulating levels of miR-29a [71].…”
Section: Mirnassupporting
confidence: 76%
“…Interestingly, exosomal miR-NAs are closely associated with the gender difference of DM. Deng et al 163 found that serum exosomal miR-29a and miR-29b displayed the diagnostic values for the pregnant women with GDM, and ROC curve analysis indicated that miR-29a combined with miR-29b (the AUC value was 0.944 [95% CI: 0.907-0.982]) for the diagnosis was prior than the single indicator (the AUC values of miR-29a and miR-29b were 0.829 [95% CI: 0.755-0.903] and 0.857 [95% CI: 0.787-0.926]). Thus, exosomal miRNAs are promising molecular biomarkers for the screening and monitoring of DM.…”
Section: Potential Clinical Applications Of Exosomal Mirnas In Dmmentioning
confidence: 99%
“…Moreover, T0 levels of HbA1c were significantly higher in GDM women in comparison to Non-GDM women. Similarly, multiple studies detected significantly higher HbA1c levels in women who developed GDM in comparison to those who completed their pregnancy free of GDM manifestations [20,21,22] . Statistical analyses defined high T0 levels of HbA1c and high ΔHbA1c as early specific discriminators for women vulnerable to development of GDM at the 24-26 th GW and paired-sample area analysis for AUC for T0 level of HbA1c and ΔHbA1c showed non-significant difference in favor of T0 level of HbA1c, so that T0 level of HbA1c could be considered as the significant early predictor for upcoming GDM, which spares time till the 12 th GW before institution of prophylactic and/or therapeutic measures.…”
Section: Discussionmentioning
confidence: 91%